Synchronization of public passenger transport subsystems using stochastic simulation: the case of lines with longer headway times - Bulíček, Josef; Drdla, Pavel; Matuška, Jaroslav (CAL-TEK SRL, 2020)
This paper is focused on timetable synchronization of urban, regional and long-distance public passenger transport subsystems in stochastic conditions. Proposed method is based on a mesoscopic simulation model. Model is applied within a process (method) leading to a robust timetable in the point of view of passengers changing e.g. from trains to buses of urban public transport. Solution is focused on specific condition – the case of relative long time headways between individual services of public transport like 30, 60 or 120 minutes, so that possible time loss can be serious. There are a number of such cases in reality. It is typical for small and medium sized cities or municipalities. Some lines with similar headway time can be found in large cities as well. Solution is illustrated by the case study focused on interchange node located in Žďár nad Sázavou (Czech Republic). Modified approach to generating of train input delays allowing to take overall operational situation on railway infrastructure into account (e.g. influence of construction works) is presented as well. This is compared to the way based on generation of delays in an individual way for individual trains.
Koordinace subsystémů veřejné osobní dopravy s využitím simulace: případ linek s delšími intervaly
Keywords: delay; interchange node; public passenger transport; simulation model; timetable synchronization; zpoždění; přestupní uzel; veřejná osobní doprava; simulační model; koordinace jízdních řádů